2021
DOI: 10.1108/ilt-01-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic lubrication effect of antioxidant and low content ZDDP on PFPE grease

Abstract: Purpose The purpose of this study is to reduce the use of Zinc dialkyl dithiophosphates (ZDDP) and improve the frictional properties and thermal oxidation stability of Perfluoropolyether (PFPE) grease by adding antioxidant additives. The addition of antioxidants can reduce the consumption of ZDDP as an antioxidant, thus improving the anti-wear efficiency of ZDDP and reducing the excess phosphorus element in the grease. Design/methodology/approach In this study, an antioxidant with good comprehensive performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…For the sake of investigating the inhibitory effect of three phenolic substances on lubricants oxidation, the reaction energy barrier of phenoxy free radicals to 3, 26-dimethyl octacosane was calculated comparing with that of alkoxy free radicals to 3, 26-dimethyl octacosane, as shown in equation ( 4)- (7). The energy barrier of alkoxy radical reaction with lubricants was 156.88 kJ/mol, and that of phenoxy free radical, 2-tert-butylphenoxy and 2,6-di-tert-butylphenoxy were 146.10 kJ/mol, 224.39 kJ/mol and 459.86 kJ/mol, respectively.…”
Section: Figure 2 Schematic Of Reaction Energy Barrier 3 Results and ...mentioning
confidence: 99%
See 2 more Smart Citations
“…For the sake of investigating the inhibitory effect of three phenolic substances on lubricants oxidation, the reaction energy barrier of phenoxy free radicals to 3, 26-dimethyl octacosane was calculated comparing with that of alkoxy free radicals to 3, 26-dimethyl octacosane, as shown in equation ( 4)- (7). The energy barrier of alkoxy radical reaction with lubricants was 156.88 kJ/mol, and that of phenoxy free radical, 2-tert-butylphenoxy and 2,6-di-tert-butylphenoxy were 146.10 kJ/mol, 224.39 kJ/mol and 459.86 kJ/mol, respectively.…”
Section: Figure 2 Schematic Of Reaction Energy Barrier 3 Results and ...mentioning
confidence: 99%
“…(5) (6) (7) In general, the hydrogen supply capacity of molecules and the stability of free radical generated by the hydrogen supply reaction are related to the bond dissociation energy of bonds for hydrogen supply and the energy difference from the HOMO to the LUMO of molecules. The lower the bond dissociation energy of O-H bond and the energy difference from the HOMO to the LUMO of molecules, the stronger its hydrogen supply capacity, and the more stable the free radical generated by the hydrogen supply reaction [12].…”
Section: Figure 2 Schematic Of Reaction Energy Barrier 3 Results and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the testing time of the UMT experiments is limited, it can only explain the high-temperature lubrication performance in a short time but long-term operation. Considering that the main failure modes of greases in high-temperature environments are oxidation deterioration and high-temperature evaporation, we have done several sets of thermal gravimetric analysis (TGA) experiments and differential scanning calorimetry (DSC) experiments of greases to judge the long-term stability of the grease in high-temperature environment (Xu et al , 2017; Zhang et al , 2021; Qi et al , 2021). Therefore, TGA and DSC experiments were done for the grease to explain its long-term lubrication performance in high temperature.…”
Section: Methodsmentioning
confidence: 99%
“…6). Qi et al [55] found that adding antioxidants to additives to reduce the antioxidant reaction of additives can enhance the temperature stability and antiwear properties of lubricating greases.…”
Section: Grease Lubricationmentioning
confidence: 99%